THE IMPLEMENTATION OF SKIMMING TECHNIQUE TOWARDS STUDENTS’ READING COMPREHENSION - Syaifudin Latif Darmawan (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
The study is to find out whether skimming technique enhance students’ reading comprehension at English Department of Muhammadiyah University of Metro, Academic Year 2015/2016. This research is conducted at English Study Program of Muhammadiyah University of Metro. The population of the research is the students of English department, while the sample of the research is the students at fourth semester of English department Muhammadiyah University of Metro. To determine the sample, the researcher employs purposive technique sampling. Then, To collect the data, the researcher used documentation, Observation, Interview and questionnaire. Furthermore, to analyze the data, the researcher apply some steps: (1) data reduction, (2) data display and (3) data conclusion. The result of research indicates that the skimming technique has significant contribution to students’ reading comprehension at fourth semester of English Study Program, Muhammadiyah University of Metro.